Design of a polyherbal mix by supercritical carbon dioxide extraction and its encapsulation by spray drying: Phytochemical properties and shelf‐life study of the encapsulate. Issue 4 (21st October 2016) - Ghosh, Sudip; Dutta, Sayantani; Kumar Ghosh, Probir; Bhattacharjee, Paramita; Das, Satadal
Abstract: A polyherbal mix of tulsi leaves, bay leaves, and small cardamom seeds powder was subjected to supercritical carbon dioxide (SC‐CO2 ) extraction. Highest yield of the extract along with the maximum antioxidant potency was obtained with a 20 g powdered mix (optimized) of 1:1:2 of tulsi leaf:bay leaf:small cardamom seed at extraction conditions of 60 °C, 300 bar, 90 min at a flow rate of 2.5 L/min of gaseous CO2 . The optimized condition of microencapsulation of the same was achieved at an inlet air temperature of 140 °C with 60:40 of maltodextrin:gum arabic as wall material. Storage stability study established this herbal encapsulate to be a promising novel natural antioxidant for food and pharmaceutical applications. Practical applications: A new method for design of polyherbal mixes using supercritical carbon dioxide (SC‐CO2 ) extraction and microencapsulation has been reported. This methodology can be adopted for formulation of newer polyherbal mixes from herbs and spices, to arrive at novel Ayurceuticals with potent therapeutic properties. The SC‐CO2 extract of powdered tulsi leaves, bay leaves, and small cardamom seeds is a classic example of an Ayurceutical with remarkably enhanced antioxidant potency than that of the individual botanicals. The microencapsulated extract of the polyherbal mix can be marketed as a "finished herbal product, " having higher storage stability than the native extract and allows controlled release of the antioxidants. Both the extract and its microencapsulate have promising applications as natural antioxidants in soybean oil, replacing the most commonly used commercial antioxidants (Ghosh, Chatterjee, Mishra, & Bhattacharjee, 2016 ).